2015
DOI: 10.1111/jnc.13289
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier and brain fatty acid uptake: Role of arachidonic acid and PGE2

Abstract: Read the full article 'Exogenous arachidonic acid mediates permeability of human brain microvessel endothelial cells through prostaglandin E 2 activation of EP 3 and EP 4 receptors' on page 867.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The PUFAs (≈Cholesterylesters) take an important place (13.61%) as well as their carriers the LPC lipid compound (5.64%) [13][14][15][16]. Interestingly, both omega-3 "fish oil" FA EPA and DHA are found in rather high concentrations respectively 0.277% and 0.258% respectively in blood plasma but not in the brain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PUFAs (≈Cholesterylesters) take an important place (13.61%) as well as their carriers the LPC lipid compound (5.64%) [13][14][15][16]. Interestingly, both omega-3 "fish oil" FA EPA and DHA are found in rather high concentrations respectively 0.277% and 0.258% respectively in blood plasma but not in the brain.…”
Section: Resultsmentioning
confidence: 99%
“…states and this might be stimulated by a physiological level of Arachidonic Acid (ARA) [13]. But probably many other compounds of mainly the Cholesteryl fraction (PUFAs) are involved, and for this reasoning we will elucidate this topic related to optional passive/active carriers in the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…The study of [10] demonstrates that the intracellular carrier protein fatty acid-binding protein 5 (FABP5) binds to DHA and is involved in the brain endothelial cell uptake and subsequent BBB transport of DHA, confirming the importance of this cytoplasmic carrier protein in the CNS exposure of this PUFA essential for neuronal function The importance of FA for the developing and adult brain has been recently reviewed [22]. In addition, recent investigations are indicative this might be stimulated by a physiological level of arachidonic acid (ARA) [23] -but probably many other compounds-that could be associated with many different physiological and pathophysiological states. In these studies an increased model of permeability model of the human blood brain barrier (BBB) in the absence of cytokines was suggested [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent investigations are indicative this might be stimulated by a physiological level of arachidonic acid (ARA) [23] -but probably many other compounds-that could be associated with many different physiological and pathophysiological states. In these studies an increased model of permeability model of the human blood brain barrier (BBB) in the absence of cytokines was suggested [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some fatty acids, like erucic acid (308, 309), suffer metabolic changes as they cross the BBB, whereas others do not (310, 311). Studies indicate that lipoproteins are hydrolyzed as they cross the BBB by the enzyme lipoprotein lipase associated to the membrane of endothelial cells (312316).…”
Section: Functions Of Non-neuronal Cellsmentioning
confidence: 99%